The Effect of Rambutan Honey Toothpaste On The Diameter Of The Inhibition Zone For The Growht Of Staphylococcus aureus - Euis Reni Yuslianti; Herryawan .Herryawan; Destiana Dewi Ramadhanty (Maranatha Christian University, 2023)
Dental plaque is a collection of bacteria embedded in an organic polymer matrix on the tooth surface, which is the main cause of most dental and oral diseases such as caries and periodontal disease. The most important thing to control the accumulation of dental plaque is to brush your teeth with the right technique using toothpaste. The movement when brushing teeth is effective in eliminating plaque, while the antibacterial composition of toothpaste is effective against plaque-forming bacteria. The potential of rambutan honey as an antibacterial agent in toothpaste has been known because honey has high osmolarity, low pH, contains hydrogen peroxide, phenolic acids, and flavonoids. The purpose of this study is to determine the effect of rambutan honey toothpaste in inhibiting the growth of Staphylococcus aureus, a bacteria that can form a biofilm and is thought to act as an pathogen of periodontal disease. This research method was an in vitro laboratory experiment with Kirby Bauer diffusion method, to test the inhibitory power of 60% rambutan honey toothpaste, toothpaste base, chloramphenicol as a positive control, and sterile aquadest as a negative control. The zone of inhibition of the growth of Staphylococcus aureus formed on Mueller Hinton Agar media was measured using a caliper. Results of this research showed that rambutan honey toothpaste had an inhibitory effect, not different from chloramphenicol (p=0.081), and different from aquadest (p=0.001), due to the antibacterial activity of honey from high osmolarity, low pH, contains hydrogen peroxide, phenolic acid, and flavonoids. Rambutan honey toothpaste was not different from the toothpaste base (p=0.096), related to its low solubility so that the spread of antibacterial was slow. It was concluded that rambutan honey toothpaste could inhibit the growth of Staphylococcus aureus, there was no difference with chloramphenicol and there was a difference with aquadest, but there was no difference with toothpaste base.